EFFECT OF MICROPLASTIC ON GREEN MUSSEL Perna viridis: EXPERIMENTAL APPROACH - Rahim, Nur Fadhilah; Yaqin, Khusnul; Rukminasari, Nita (Jurnal Ilmu Kelautan SPERMONDE, 2019)
Plastics become debris in the ocean that can be broken down into tiny particles of micro size (<5 mm) and scattered into columns to the bottom of the water. Its very small size makes it easily accessible to various aquatic organisms, such as plankton, crustacean, and mussel. There have been many studies use mussel as a bioindicator for microplastic pollution but no one has observed the effect of microplastic exposure to mussel mortality. The aim of study was to examine the effect of microplastic on mussel mortality. Green mussels were collected from Mandalle Waters, Pangkep Regency (Pangkajene Kepualauan) then were exposed to microplastic polyethylene originating from shieving of scrub soap. The exposure was carried out for 7 days with microplastic concentrations of 0.05 (A), 0.5 (B), and 5 (C) g/L. Statistical test results showed the treatment B and C were not significantly different, but the two treatment were significantly different from treatment A. The percentage of green mussel mortality during the experiment increased with increasing microplastic concentrations with the percentage of mortality exceeding 80% at treatment C.